Effect of Vitamin E as α-Tocopherol Acetate on Mercuric Chloride-Induced Chronic Oxidoreductive Stress and Nephrotoxicity in Rats: تاثير استخدام فيتامين هاء كألفا- توكوفيرول اسيتيت على حالة الجهد التاكسدي الاختزالي الناشيء عن المحدث كلوريد الزئبقيك والمتسبب في حالة التسمم الكلوي في الجرذان - Muhammad Assumaidaee, Ajwad Awad; Ali, Nathera M.; Fadhil, Ammar A. (The Iraqi Journal of Veterinary Medicine, 2019)
Impact of vitamin E against mercuric chloride (HgCL2) induced renal toxicity in Wister albino rats was studied. Feeding of the rats with diet and water contaminated with a non lethal dose of the mercuric chloride (20 parts per million) every other day for 42 days resulted in significant increase of serum malondialdehyde (MDA), which is an important biomarker of the oxidoreductive stress, and significant decline in each of the reduced glutathione (r-GSH) concentration, glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) enzymes activities, which constitute a vital part of the endogenous protective antioxidant system, as compared to the control group. The study found that the simultaneous oral co administration of vitamin E (as α-tocopherol acetate) 100 mg/kg B.W. every other day for 42 days along with mercuric chloride produced a cardinal protective effects against the development of the mercuric chloride induced nephrotoxicity. This can be through reversing the elevated oxidative stress; induced by the administration of the HgCL2. In conclusion serum biochemical and kidney histopathological findings of the current study highlight the beneficial effects of vitamin E in rats with HgCl2-mediated renal toxicity.